Big data benchmarking : 5th International Workshop, WBDB 2014, Potsdam, Germany, August 5-6- 2014, Revised selected papers /: 5th International Workshop, WBDB 2014, Potsdam, Germany, August 5-6- 2014, Revised selected papers. (2015) - Unknown
No abstract available